IMPLEMENTASI WEB LAUNDRY DENGAN METODE AGILE UNTUK MENINGKATKAN EFISIENSI - Illahi, Rendy Rahmad; Hutabri, Ellbert (JURNAL ILMIAH INFORMATIKA, 2025)
Rapid developments in industry and information technology have created increasingly fierce competition to create new innovations and maintain competitiveness in the global marketplace. The development of information systems is currently rapid and dynamic, with many people relying on them to simplify their work activities. One of the easiest forms of information systems to develop is a web-based information system. This research aims to develop a web-based information system for Khendy Laundry. Currently, Khendy Laundry still uses a traditional system, namely manual recording and transactions using paper receipts. With this method, customer and order data are sometimes lost due to damaged or lost receipts, so the main goal is to record transactions digitally. The research method used is the Agile method. The results show that this new system successfully reduces the risk of errors and data loss, speeds up, and simplifies report generation. This system improves operational efficiency at the laundry.